Characterization of Space Charge Accumulations in Alternative Gas-to-Liquid Oil-Immersed Paper Insulation Under Polarity Reversal Voltage Scenarios - Ya Wang; Yifei Xiong; Zheming Wang; Wu Lu (Energies)
Due to its advantages, such as its corrosive sulfur-free property and high purity, gas-to-liquid (GTL) oil is regarded as an excellent alternative to conventional naphthenic mineral oil in the oil/paper composite insulation of UHV converter transformers. In such application scenarios, under the condition of voltage polarity reversal, charge accumulation is likely to occur along the liquid/solid interface, which leads to the distortion of the electric field, consequently reducing the breakdown voltage of the insulating material, and leading to flashover in the worst case. Therefore, understanding such space charge characteristics under polarity-reversed voltage is key for the insulation optimization of GTL oil-filled converter transformers. In this paper, a typical GTL oil is taken as the research object with naphthenic oil as the benchmark. Electroacoustic pulse measurement technology is used to study the space charge accumulation characteristics and electric field distribution of different oil-impregnated paper insulations under polarity-reversed conditions. The experimental results show that under positive–negative–positive polarity reversal voltage, the gas-impregnated pressboard exhibits significantly higher rates of space charge density variation and electric field distortion compared with mineral oil-impregnated paper. In stage B, the dissipation rate of negative charges at the grounded electrode in GTL oil-impregnated paper is 140% faster than that in mineral oil-impregnated paper. In stage C, the electric field distortion rate near the electrode of GTL oil-impregnated paper reaches 54.15%. Finally, based on the bipolar charge transport model, the microscopic processes responsible for the differences in two types of oil-immersed papers are discussed.